Ethical and Sustainable AI Adoption in Future Global Business Practices - Winanto, Sujoko (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Artificial intelligence (AI) has become a transformative force in global business, offering unprecedented opportunities for innovation and efficiency while simultaneously raising complex ethical and sustainability challenges. This study explores how ethical principles and sustainability frameworks can be integrated into AI-driven business practices, emphasizing the dual imperative of technological advancement and responsible governance. Employing a qualitative research design with a library research approach and content analysis, the study systematically reviews academic literature, policy documents, and institutional reports published between 2020 and 2025. Findings highlight key ethical issues including fairness, accountability, transparency, and privacy, as well as sustainability dimensions related to environmental impact, economic inclusivity, and social equity. The analysis further reveals that while global regulatory frameworks such as the OECD AI Principles and UNESCO recommendations provide valuable guidance, governance remains fragmented and often lags behind technological innovation. Importantly, the study identifies a research gap in integrative scholarship that simultaneously addresses ethical and sustainability concerns in business adoption of AI. The results suggest that embedding ethical and sustainable AI into corporate strategies is essential not only for compliance but also for building resilience, fostering stakeholder trust, and achieving long-term competitiveness. This research contributes to academic discourse by offering a comprehensive framework for aligning AI innovation with global ethical and sustainability objectives, while also providing practical insights for policymakers, corporations, and international organizations.